2020
DOI: 10.3389/fgene.2019.01360
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling Reveals the Regulatory Role of CXCL8 in Promoting Colorectal Cancer

Abstract: C-X-C motif chemokine ligand 8 (CXCL8) is involved in tumor proliferation, migration, and invasion. However, the function of CXCL8 in colorectal cancer (CRC) is controversial. Here, we analyzed RNA-sequencing (RNA-seq) data to identify differentially expressed genes and pathways according to gene ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways associated with CRC. The levels of the mRNA encoding CXCL8 were significantly increased in early and advanced stages of CRC, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
5
16
0
Order By: Relevance
“…On the contrary, overexpression of CXCL8 promoted proliferation, migration, and invasion of CRC cells, which was strongly correlated with CRC angiogenesis, metastasis, poor prognosis, and disease-free survival [44,45]. However, high expression of CXCL8 could act as a protective barrier for liver metastasis of CRC and coincide with better prognosis [46,47]. Objectively, the role of CXCL8 still remained in dispute.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, overexpression of CXCL8 promoted proliferation, migration, and invasion of CRC cells, which was strongly correlated with CRC angiogenesis, metastasis, poor prognosis, and disease-free survival [44,45]. However, high expression of CXCL8 could act as a protective barrier for liver metastasis of CRC and coincide with better prognosis [46,47]. Objectively, the role of CXCL8 still remained in dispute.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL8, also known as interleukin-8, is a member of the chemokine family and is involved in inflammation and immune response (5). Previous studies have revealed an abnormal high expression of CXCL8 in malignant tumors, which is mainly involved in tumor cell growth, apoptosis, invasion, and migration (6)(7)(8)(9)(10)(11)(12). Large-scale cohort studies have suggested that elevated plasma or serum CXCL8 was associated with worse prognosis in melanoma, metastatic urothelial carcinoma, and renal cell carcinoma patients (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…In CRC, we found that Anaerolineae and TM7 , oral microbes that also inhabit the human gastrointestinal tract, and are known to promote oral and colorectal tumorigenesis 7276 , are negatively correlated with host genes enriched for tumor-promoting Interleukin-10 signaling pathway, such CXCL8 and IL1RN ( Figure 3C and Supplementary Figure S2). CXCL8 is known to be overexpressed in CRC, and IL1RN is centrally involved in immune and inflammatory response, and its polymorphisms are implicated in colorectal carcinogenesis 7779 . Other host genes in Interleukin-10 signaling, such as CCR2 and FPR1 , are positively correlated with Bacteroidales ( Figure 3C and Supplementary Figure S2).…”
Section: Resultsmentioning
confidence: 99%